Historis Konsep Prapengetahuan Allah dan Hubungannya dengan Predestinasi (Dari Abad Ke 11-15) - Ziduhu Laia, Harman; Donald Sugiarto , Thio (Kaluteros Jurnal Teologi Dan Pendidikan Agama Kristen, 2024)
The concept of God's foreknowledge and its relationship with predestination is one of the teachings in the Bible that is difficult to understand. Discussing the foreknowledge and predestination of God entails delving into the divine plan for humanity throughout eternity. Consequently, it has been subject to much speculation. The difficulty lies in affirming that it can only be comprehended to the extent that God reveals it in the Bible. Even biblical statements about it have been interpreted diversely. This is evidenced by the various views held by theologians from the 11th to the 15th century. Based on a literature review of these theologians, it is apparent that the foreknowledge of God has been understood in several senses: as God's foreknowledge of all things and causing predestination; as God's approval of the chosen ones and causing predestination; as predestination itself for the saved; and as God's foreknowledge of what He will do for believers, occurring simultaneously with predestination, both being caused by the will of God.